Using videos in a smartphone app logbook to aid obstetricians and gynaecologists with reflection following critical events. (20th April 2018) - Gray, Thomas G; Li, Weiguang; Farrell, Tom
Abstract : Introduction: Reflection is essential for continuous professional development. Many opportunities to reflect during training in obstetrics and gynaecology are not utilised. A Smartphone App ( Healthcare Supervision Logbook ), allows doctors training in obstetrics and gynaecology to view videos to aid reflection. The App incorporates a comprehensive logbook of practical skills. A self-facilitated reflective process, prompted by offering the viewing of a video when logging an event such as a shoulder dystocia, has been integrated into the logbook. The objective of this study was to evaluate how this function aids reflection. Methods: Forty doctors training in obstetrics and gynaecology undertook a shoulder dystocia drill as part of a mock examination. After completing the drill, participants scored their performance on a proforma, before watching a video of simulated standard management for shoulder dystocia on a Smartphone. Participants then re-scored themselves before completing a survey. This assessed their agreement with three statements on a five-point Likert scale. Results: 50% of participants marked themselves lower after watching the video. 100% agreed or strongly agreed that watching the video helped them reflect on the shoulder dystocia drill. 80% agreed or strongly agreed that they would feel more prepared to deal with shoulder dystocia as a result of using the video to reflect. 93% agreed or strongly agreed that they would be willing to use a Smartphone App with videos to aid reflection following critical events. Student's t test showed that viewing the standardised video clip on the App resulted in a significant down-marking (P<0.0005). Conclusions: Many emergency scenarios in obstetrics and gynaecology unfold quickly and are rapidly resolved, doctors-in-training need to use opportunities for self-directed reflection. Using the video self-reflection function integrated into Healthcare Supervision Logbook Smartphone App could help to prompt this process, which could be utilised in other specialities and disciplines.